The Joint Declaration on the Doctrine of Justification and Social Ethics - Peter D. Langerman (Verbum et Ecclesia, 2021)
The Joint Declaration on the Doctrine of Justification (JDDJ) developed out of understanding of the doctrine of justification and how that doctrine relates to social ethics. The article briefly describes how the doctrine of justification and sanctification developed in various traditions and how it came to be seen in the liberal theological context of the late 19th century before a corrective in the middle of the 20th century. I examine the way in which the doctrine has been criticised by oppressed persons and how we might respond to those criticisms. Finally, a way forward is suggested that might help us to apply the significant gains of the JDDJ to the whole sphere of social ethics for us here in South Africa.